The effect of difference in saliva pH against Hg release from amalgam restoration on in vitro research - Megasari, Oksana (Padjadjaran Journal of Dentistry, 2007)
Hg release from amalgam restoration is continuos as long as an amalgam in the mouth. The difference in saliva pH is one factor that influences Hg releasing from amalgam restoration. The purpose of this research was to find data the effect of the difference in saliva pH against Hg release from amalgam restoration. This research was a true experimental in vitro research. This research used 40 samples of premolar teeth of the maxilla, prepared in occlusal Class I, restored with amalgam and then divided into 4 Groups. Teeth belonging to Group 1 were immersed in saliva artificial with a pH content 5, Group 2 with a pH content of 6, Group 3 with a pH content of 7 as a control, and Group 4 with a pH content of 8. All tooth Groups were immersed for one week after condensation. Research data results analyzed using the One-Way Analysis of Variance (ANOVA). Research results measured using the Atomic Absorption Spectrophotometry (AAS) indicated that Group 1 with a pH content of 5 had the highest average release, namely, 19,276 ppb, followed by Group 4 with a pH content of 8, with a Hg release of 17,691 ppb, followed by Group 3 with a pH content of 7 as a control, with a Hg release of 13,702 ppb, and Group 2 with a pH content of 6 the lowest Hg release, namely 12,377 ppb. Summary of this research showed that there was no effect of saliva pH difference against Hg release from amalgam restoration.